High-toughness polyester low stretch yarn and preparation method thereof

By adding polyvinyl butyral resin and phenylatic dianhydride to the polyester, and using surface-treated iron powder and carboxymethyl cellulose, the brittleness and anti-static problems of polyester low-elastic wire are solved, improving the The toughness and antistatic properties of the fibers improve the comfort and service life of the clothes.

CN119162690APending Publication Date: 2024-12-20杭州东南纺织有限公司
View PDF 0 Cites 0 Cited by

Patent Information

Application Number
CN202411256377.3
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-09-09
Publication Date
2024-12-20

AI Technical Summary

Technical Problem

During the molding and processing process, the brittleness increases and toughness becomes worse due to the shortening of production cycle, and the clothing is not comfortable and anti-static.

Method used

Improve the fiber by adding polyvinyl butyral resin and phenylatic dianhydride to the polyester, blending the surface-treated iron red powder, and using carboxymethyl cellulose and nano zinc oxide in the masterbatch. Thermal conductivity and conductivity improve the toughness and antistatic properties of the fiber.

Benefits of technology

It enhances the toughness and anti-static properties of polyester low-elastic wire, improves the wear comfort and service life of clothes, and reduces the generation of static electricity.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure BDA0005034219480000041
    Figure BDA0005034219480000041
  • Figure BDA0005034219480000051
    Figure BDA0005034219480000051
  • Figure BDA0005034219480000071
    Figure BDA0005034219480000071
Patent Text Reader

Abstract

The invention belongs to the technical field of polyester low stretch yarn production, and discloses a high-toughness polyester low stretch yarn and a preparation method thereof. The high-toughness polyester low stretch yarn comprises polyester chips and color master batches, and the polyester chips are modified polyester and are prepared from terephthalic acid, ethylene glycol, polyvinyl butyral resin, iron oxide red powder, pyromellitic dianhydride and antimony catalysts. The color master batch is prepared from the following raw materials: polyvinyl chloride, carboxymethyl cellulose, nano zinc oxide, a coupling agent, a dispersing agent and a coloring agent. The preparation method of the high-toughness polyester low stretch yarn comprises the following steps that polyester chips and color master batches are mixed and melted to prepare a spinning melt, the spinning melt is extruded and spun through a spinneret plate to prepare POY yarn, the POY yarn is subjected to heating deformation, cooling, false twisting, oiling and winding, and the high-toughness polyester yarn is prepared. The prepared polyester low stretch yarn has high toughness, good hand feeling and excellent antistatic property, the preparation method is simple and easy to implement, raw materials are low in price, and the polyester low stretch yarn is suitable for industrial popularization.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The present application relates to the technical field of polyester low-stretch yarn production, and in particular to a high-tenacity polyester low-stretch yarn and a preparation method thereof. Background Art

[0002] As one of the three main fibers in synthetic fibers, polyester is widely used in clothing fabrics and other non-clothing fields due to its excellent physical and chemical properties. Since its launch, polyester products have been used as the main textile raw material to weave various textiles due to their good drape, high strength, crispness and wrinkle resistance.

[0003] Polyester low-elastic yarn is produced by continuous polyester production, esterification reaction of raw materials such as terephthalic acid and ethylene glycol, and then polycondensation to prepare polyester melt for direct spinning, and the POY-DTY process is mostly used for preparation. Polyester low-elastic yarn is made of polyester polymer materials through spinning and stretching processes. During the molding process, the production cycle needs to be shortened and the molding temperature is high, so that the produced polyester low-elastic yarn material is easy to show brittleness and poor toughness, resulting in the service life of the polyester low-elastic yarn being affected. In addition, another technical problem is that the clothing made of polyester low-elastic yarn needs to be improved in terms of wearing comfort, and the antistatic ability of polyester yarn itself is also poor. When the clothing made of polyester low-elastic yarn is rubbed, it is easy to generate static electricity, so that the dust in the air is easily adsorbed on the polyester low-elastic yarn clothing, further affecting the service life and wearing comfort of the polyester low-elastic yarn clothing. Therefore, the development of a polyester low-elastic yarn with good toughness, smoother surface and certain antistatic effect is of great practical significance for improving the quality of life and industrial production. Summary of the invention

[0004] In order to solve the problems of poor toughness and wearing comfort of the current polyester low-stretch yarn during use, a polyester low-stretch yarn with good toughness, smoother surface and certain antistatic effect is developed. The present application provides a high-toughness polyester low-stretch yarn and a preparation method.

[0005] In a first aspect, the present application provides a high-tenacity polyester low-stretch yarn, comprising polyester chips and masterbatches in a weight ratio of 3-8:100; The polyester chips are modified polyesters, comprising the following raw materials in parts by weight: 80-110 parts of terephthalic acid, 35-55 parts of ethylene glycol, 5-10 parts of polyvinyl butyral resin, 2-5 parts of iron oxide red powder, 7-12 parts of pyromellitic anhydride, and 1-3 parts of antimony catalysts; the masterbatch comprises the following raw materials in parts by weight: 20-30 parts of polyvinyl chloride, 10-15 parts of carboxymethyl cellulose, 2-3 parts of nano zinc oxide, 1-2 parts of coupling agents, 1-3 parts of dispersants, and 3-6 parts of colorants.

[0006] By adopting the above technical scheme, the iron red powder is added to the polyester reaction system in the present application, and does not participate in the polymer synthesis reaction of esterification and polycondensation, nor does it affect the catalytic effect of the catalyst in the esterification and polycondensation process of polyethylene terephthalate. It is evenly distributed in the polymer melt, which greatly improves the heat conduction efficiency between fibers. Therefore, the difference in fiber thermal shrinkage rate can be reduced on the existing traditional polyester fiber post-processing device, and the uniformity of fiber tensile strength can be improved, thereby enhancing the toughness of the obtained polyester low-elastic yarn; secondly, the iron red powder has a high dispersion uniformity in polyester, which can effectively promote polyester crystallization, accelerate the crystallization rate, and effectively improve its thermodynamic stability. The molecules in the fiber with good crystallinity are more neatly arranged, and have better mechanical properties. Under the premise of reducing the brittleness of the fiber, it can effectively ensure that the fiber breaking strength and initial modulus are at a high level; carboxymethyl cellulose and polyvinyl butyral resin have a strong hygroscopic effect, which is conducive to the polyester yarn absorbing moisture in the air and reducing the generation of static electricity. The coupling agent can also enhance the conductivity of the polyester yarn under the action of iron red powder and nano zinc oxide, thereby improving its antistatic property.

[0007] Optionally, the antimony-based catalyst is selected from antimony trioxide, antimony glycol or antimony acetate.

[0008] Optionally, the iron ore red powder is pretreated modified iron ore red powder, and the pretreatment process includes the following steps: adding phosphoric acid into acetone, stirring, adding iron ore red powder and stirring, and drying to obtain the modified iron ore red powder.

[0009] Optionally, the iron ore red powder is a pretreated modified iron ore red powder, and the pretreatment process includes the following steps: adding phosphoric acid to acetone, stirring, adding iron ore red powder and stirring, baking at 60-80°C for 1-2h to dry it, and obtaining modified iron ore red powder; wherein the weight ratio of the phosphoric acid, acetone and iron ore red powder is 0.1-1:5-10:20.

[0010] By adopting the above technical scheme, the iron ore red powder is surface-modified by using phosphoric acid so that the surface of the iron ore red powder particles can carry more active groups, thereby improving the dispersion ability of the iron ore red powder in the polyester system; secondly, it is beneficial to control the particle size and morphology of the iron ore red powder and promote the uniform dispersion of the iron ore red powder in the polyester system. Finally, after the surface modification of the iron ore red powder, it is beneficial to save the amount of iron ore red powder, and similar technical effects can be achieved by using less modified iron ore red powder.

[0011] Optionally, the raw materials of the polyester chips further include 5-9 parts by weight of glutaric acid and 10-18 parts by weight of dimethylsilanediol.

[0012] Optionally, the raw materials of the polyester chips further include 5-9 parts by weight of glutaric acid.

[0013] Optionally, the raw materials of the polyester chips further include 10-18 parts by weight of dimethylsilanediol.

[0014] Optionally, the method for preparing the polyester chips comprises the following steps: Add iron oxide red powder to one-half amount of ethylene glycol for ultrasonic dispersion to obtain a suspension, mix the remaining raw materials in a reaction container, carry out esterification reaction, control the pressure to be normal pressure, react at 250-300°C for 3-5h, add the suspension dropwise during the reaction, and control the dropping time to be 0.5-1h; then carry out polycondensation reaction, increase the pressure to 1000-1200Pa, react at 250-280°C for 2-3h to obtain a spinning melt, solidify, stretch, wind, slice, and dry to obtain polyester slices.

[0015] Optionally, the method for preparing the masterbatch comprises the following steps: The raw materials are added into a reaction container and mixed and stirred at 70-90° C. for 10-30 minutes. The mixed materials are added into a twin-screw extruder for melting. The melting temperature is controlled at 150-200° C. and the screw speed is 250-300 r / min. The materials are extruded, cooled, pelletized and dried to obtain masterbatch.

[0016] In a second aspect, the present application provides a method for preparing the above-mentioned high-tenacity polyester low-elastic yarn, comprising the following steps: S1, mixing polyester chips and masterbatch and sending them into an extruder for melting to obtain a spinning melt; S2, filtering the spinning melt obtained in step S1, pumping, extruding and spinning through a spinneret, and cooling to obtain POY yarn; S3, guiding, heating and deforming, cooling, false twisting, and winding the POY yarn obtained in step S2 to obtain high-tenacity polyester yarn.

[0017] Optionally, in step S2, during the spinneret extrusion process, the spinning temperature is controlled to be 260-300°C, and the cooling temperature is controlled to be 15-25°C.

[0018] Optionally, in step S3, the stretching ratio is controlled to be 2-5 and the processing speed is controlled to be 500-800 m / min during the heating deformation process.

[0019] Optionally, in step S3, oiling is performed after false twisting, and the oiling rate is controlled to be 0.3-0.8wt%.

[0020] Optionally, the oiling agent used in the oiling in step S3 includes triphenyl phosphate, polyethylene glycol dioleate and castor oil polyoxyethylene ether in a weight ratio of 2-3:10-20:5-10.

[0021] In summary, the present invention includes at least one of the following beneficial technical effects: 1. In this application, polyvinyl butyral resin and pyromellitic anhydride are added to polyester to weaken the interaction between the molecular chains of polyester fibers, thereby making the polyester low-elastic yarn products more elastic and better in feel; at the same time, the structure of the polyester low-elastic yarn can be changed to have better tensile and bending properties; in this application, the surface-treated iron red powder is added to the polyester reaction system, which greatly improves the thermal conductivity between the polyester fibers, can improve the thermodynamic stability of the obtained polyester low-elastic yarn, make the molecular arrangement in the fiber more orderly, and have better toughness. The polyvinyl butyral resin in the polyester slice and the carboxymethyl cellulose in the masterbatch are compounded, which has a strong hygroscopic effect, which is conducive to the polyester yarn absorbing moisture in the air and reducing the generation of static electricity. The coupling agent, iron red powder and nano zinc oxide can also enhance the conductivity of the polyester yarn under the joint action, thereby improving the antistatic property of the polyester low-elastic yarn.

[0022] 2. The preparation method of the polyester low-elastic yarn in this application is simple and easy to implement, the raw materials are cheap, and it is suitable for industrial promotion. DETAILED DESCRIPTION

[0023] The present application designs a high-tenacity polyester low-elastic yarn, including polyester chips and masterbatches in a weight ratio of 3-8:100; The polyester chips are modified polyesters, comprising the following raw materials in parts by weight: 80-110 parts of terephthalic acid, 35-55 parts of ethylene glycol, 5-10 parts of polyvinyl butyral resin, 2-5 parts of iron oxide red powder, 7-12 parts of pyromellitic anhydride, and 1-3 parts of a catalyst; The masterbatch comprises the following raw materials in parts by weight: 20-30 parts of polyvinyl chloride, 10-15 parts of carboxymethyl cellulose, 2-3 parts of nano zinc oxide, 1-2 parts of coupling agent, 1-3 parts of dispersant and 3-6 parts of colorant.

[0024] The high-tenacity polyester low-elastic yarn of the present application is prepared by the following method, comprising the following steps: S1, mixing polyester chips and masterbatch and sending them into an extruder for melting to obtain a spinning melt; S2, filtering the spinning melt obtained in the step S1, pumping, extruding and spinning through a spinneret, and cooling to obtain POY yarn; S3, guiding, heating and deforming, cooling, false twisting, and winding the POY yarn obtained in the step S2 to obtain high-tenacity polyester yarn.

[0025] The technical problem solved by the present application is that the polyester low-elastic yarn molding process needs to shorten the production cycle and thus uses a higher molding temperature, which makes the produced polyester low-elastic yarn material easy to show brittleness and poor toughness, resulting in the service life of the polyester low-elastic yarn being affected. Another problem is that the wearing comfort of clothing made of polyester low-elastic yarn needs to be improved, and the antistatic ability of the polyester yarn itself is also poor. The present application adds polyvinyl butyral resin and pyromellitic dianhydride to polyester, so that the polyester low-elastic yarn products become more elastic and feel better; in the present application, the surface-treated iron red powder is added to the polyester reaction system, which greatly improves the heat conduction efficiency between polyester fibers and makes the fibers have better toughness; polyvinyl butyral resin and carboxymethyl cellulose in the masterbatch are compounded to improve the antistatic property.

[0026] The present application is further described in detail below in conjunction with specific embodiments.

[0027] Preparation Example 1-5 Preparation Examples 1-5 are polyester chips made from different raw materials, the difference being that the raw material ratios are different, as shown in Table 1 (unit: parts by weight).

[0028] Table 1 The polyvinyl butyral resin in Preparation Example 1-5 was purchased from Sichuan Dongcai Technology, and the product model is DFM0819-A.

[0029] The particle size of the iron ore red powder in Preparation Example 1-5 is 400 mesh.

[0030] The pyromellitic dianhydride in Preparation Example 1-5 was purchased from Condis Chemical with a CAS number of 89-32-7.

[0031] The antimony catalyst used in Preparation Example 1-5 is ethylene glycol antimony, with a CAS number of 29736-75-2.

[0032] The preparation method of the polyester chips in Preparation Example 1-5 comprises the following steps: Add iron oxide red powder to half of the amount of ethylene glycol for ultrasonic dispersion to obtain a 10wt% suspension, mix the remaining raw materials in a reaction container, and carry out esterification reaction. The pressure is controlled to be normal pressure, and the reaction is carried out at 280°C for 3 hours. The suspension is added dropwise during the reaction, and the dropping time is controlled to be 1 hour. Then, a condensation reaction is carried out, the pressure is increased to 1200Pa, and the reaction is carried out at 260°C for 3 hours to obtain a spinning melt, which is then solidified, stretched, wound, sliced, and dried to obtain polyester chips.

[0033] Preparation Example 6 Preparation Example 6 is based on Preparation Example 2, except that the iron oxide red powder in Preparation Example 6 is surface-modified iron oxide red powder, and the specific modification process includes the following steps: Phosphoric acid is added to acetone and stirred evenly, iron red powder is added and stirred, and the mixture is allowed to stand for 30 minutes, and baked at 80° C. for 2 hours to dry the iron red powder to obtain modified iron red powder; wherein the weight ratio of the phosphoric acid, acetone and iron red powder is 0.5:8:20.

[0034] Preparation Example 7-9 Preparation Example 7 is based on Preparation Example 6, with the difference that the raw materials of the polyester chips in Preparation Example 7 also include 7 parts by weight of glutaric acid.

[0035] Preparation Example 8 is based on Preparation Example 6, except that the raw materials of the polyester chips in Preparation Example 8 also include 15 parts by weight of dimethylsilanediol.

[0036] Preparation Example 9 is based on Preparation Example 6, except that the raw materials of the polyester chips in Preparation Example 9 further include 7 parts by weight of glutaric acid and 15 parts by weight of dimethylsilanediol.

[0037] Preparation Example 10-12 Preparation Examples 10-12 are masterbatches made from different raw materials, the difference being that the raw material ratios are different, as shown in Table 2.

[0038] Table 2 The particle size of the nano zinc oxide used in Preparation Examples 10-12 is 400 mesh.

[0039] The coupling agent used in Preparation Example 10-12 is KH-550.

[0040] The dispersant used in Preparation Examples 10-12 was sodium stearate.

[0041] The polyvinyl chloride used in Preparation Examples 10-12 was purchased from Shandong Qilu Petrochemical Co., Ltd. with a model number of SK-1000.

[0042] The preparation method of the masterbatch in Preparation Examples 10-12 comprises the following steps: The raw materials were added into a reaction container and mixed at 80°C for 15 minutes. The mixed materials were added into a twin-screw extruder for melting. The melting temperature was controlled at -200°C and the screw speed was 250r / min. The materials were extruded, cooled, pelletized and dried to obtain masterbatch.

[0043] Embodiment 1-11 Examples 1-11 are high-tenacity polyester low-elastic yarns made with different raw material ratios, and the specific ratios are shown in Table 3.

[0044] The raw materials of Examples 1-11 include polyester chips and masterbatches in a weight ratio of 6:100.

[0045] Table 3 Polyester chips Masterbatch Example 1 Preparation Example 1 Preparation Example 11 Example 2 Preparation Example 2 Preparation Example 11 Example 3 Preparation Example 3 Preparation Example 11 Example 4 Preparation Example 4 Preparation Example 11 Example 5 Preparation Example 5 Preparation Example 11 Example 6 Preparation Example 6 Preparation Example 11 Example 7 Preparation Example 7 Preparation Example 11 Example 8 Preparation Example 8 Preparation Example 11 Example 9 Preparation Example 9 Preparation Example 11 Example 10 Preparation Example 2 Preparation Example 10 Embodiment 11 Preparation Example 2 Preparation Example 12 Examples 12-13 Example 12 is based on Example 6, with the difference that the raw materials of Example 12 include polyester chips and masterbatches in a weight ratio of 3:100.

[0046] Example 13 is based on Example 6, except that the raw materials of Example 13 include polyester chips and masterbatches in a weight ratio of 8:100.

[0047] The preparation method of the high-tenacity polyester low-elastic yarn in Examples 1-13 comprises the following steps: S1, mixing polyester chips and masterbatch and sending them into an extruder for melting to obtain a spinning melt; S2, filtering the spinning melt obtained in step S1, pumping, extruding and spinning through a spinneret, during the extrusion process of the spinneret, controlling the spinning temperature to be 280° C.; cooling, controlling the cooling temperature to be 20° C.; and obtaining POY yarn; S3, guiding the POY yarn obtained in the step S2, heating and deforming, controlling the stretching ratio to 4 during the heating and deformation process, and controlling the processing speed to 500-800m / min; cooling, controlling the cooling temperature to 20°C; false twisting, oiling after false twisting, controlling the oiling rate to be about 0.6wt%, and winding to obtain high-tenacity polyester yarn.

[0048] The oiling agent used in the oiling in step S3 includes triphenyl phosphate, polyethylene glycol dioleate and castor oil polyoxyethylene ether in a weight ratio of 2:12:8.

[0049] Comparative Example 1-2 Comparative Example 1 is based on Example 6, except that no polyvinyl butyral resin is added to the raw materials of the polyester chips in Comparative Example 1.

[0050] Comparative Example 2 is based on Example 6, except that the iron oxide red powder in the raw material of the polyester chips in Comparative Example 2 is replaced by silicon dioxide particles of the same particle size.

[0051] Performance Testing The polyester low-elastic yarn prepared in Examples 1-13 and Comparative Examples 1-2 was spun, the yarn count was 40S, the yarn twist coefficient was 330, the yarn coil length was 200MM / 100 needles, and the obtained yarn was knitted into a knitted grey cloth using a weft-knitted circular knitted double rib machine.

[0052] 1. According to the standard GB / T 12703.2-2009 "Evaluation of electrostatic properties of textiles Part 2: Charge surface density", the antistatic test was carried out on the grey fabrics prepared from polyester low-stretch yarn in Examples 1-13 and Comparative Examples 1-2. The charge surface density (μC / m 2 ) is smaller, the better the antistatic performance.

[0053] 2. According to the standard GB / T3923.1-1997 "Tensile properties of textile fabrics - Part 1: Strip method for determination of breaking strength and breaking elongation", the test was carried out on a HD026n electronic fabric strength tester; the polyester low-elastic yarns in Examples 1-13 and Comparative Examples 1-2 were taken, and multiple low-elastic yarns were combined into test strips with a width of 55 mm and a length of 300 mm. Five samples were tested for each Example and each Comparative Example, and the average value was taken.

[0054] The test results are shown in Table 4.

[0055] Table 4 By analyzing the data in Table 4, it can be found that the knitted fabric made of the polyester low-elastic yarn prepared in the present application has higher breaking strength and breaking elongation; at the same time, after no polyvinyl butyral resin is added or the iron red powder is replaced with other fillers in Comparative Examples 1-2, the charge surface density of the knitted fabric made of the polyester low-elastic yarn is greatly increased. It can be seen that the polyester low-elastic yarn prepared in the present application has higher toughness and better antistatic effect.

[0056] The above are all preferred embodiments of the present application, and the protection scope of the present application is not limited thereto. Therefore, any equivalent changes made according to the structure, shape, and principle of the present application should be included in the protection scope of the present application.

Claims

1. A high-tenacity polyester low-elastic yarn, characterized in that: It includes polyester chips and masterbatches in a weight ratio of 3-8:100; The polyester chips are modified polyesters, comprising the following raw materials in parts by weight: 80-110 parts of terephthalic acid, 35-55 parts of ethylene glycol, 5-10 parts of polyvinyl butyral resin, 2-5 parts of iron oxide red powder, 7-12 parts of pyromellitic anhydride, and 1-3 parts of antimony catalyst; The masterbatch comprises the following raw materials in parts by weight: 20-30 parts of polyvinyl chloride, 10-15 parts of carboxymethyl cellulose, 2-3 parts of nano zinc oxide, 1-2 parts of coupling agent, 1-3 parts of dispersant and 3-6 parts of colorant.

2. The high-tenacity polyester low-elastic yarn according to claim 1, characterized in that: The iron red powder is pretreated modified iron red powder, and the pretreatment process comprises the following steps: adding phosphoric acid into acetone, stirring, adding iron red powder and stirring, and drying to obtain the modified iron red powder.

3. The high-tenacity polyester low-elastic yarn according to claim 1, characterized in that: The raw materials of the polyester chips also include 5-9 parts by weight of glutaric acid and / or 10-18 parts by weight of dimethylsilanediol.

4. The high-tenacity polyester low-elastic yarn according to claim 1, characterized in that: The preparation method of the polyester chip comprises the following steps: Add iron oxide red powder to one-half amount of ethylene glycol for ultrasonic dispersion to obtain a suspension, mix the remaining raw materials in a reaction container, carry out esterification reaction, control the pressure to be normal pressure, react at 250-300°C for 3-5h, add the suspension dropwise during the reaction, and control the dropping time to be 0.5-1h; then carry out polycondensation reaction, increase the pressure to 1000-1200Pa, react at 250-280°C for 2-3h to obtain a spinning melt, solidify, stretch, wind, slice, and dry to obtain polyester slices.

5. The high-tenacity polyester low-elastic yarn according to claim 1, characterized in that: The preparation method of the masterbatch comprises the following steps: The raw materials are added into a reaction container and mixed and stirred at 70-90° C. for 10-30 minutes. The mixed materials are added into a twin-screw extruder for melting. The melting temperature is controlled at 150-200° C. and the screw speed is 250-300 r / min. The materials are extruded, cooled, pelletized and dried to obtain masterbatch.

6. A method for preparing the high-tenacity polyester low-elastic yarn according to any one of claims 1 to 5, characterized in that: The following steps are involved: S1, mixing polyester chips and masterbatch and sending them into an extruder for melting to obtain a spinning melt; S2, filtering the spinning melt obtained in step S1, pumping, extruding and spinning through a spinneret, and cooling to obtain POY yarn; S3, guiding, heating and deforming, cooling, false twisting, and winding the POY yarn obtained in step S2 to obtain high-tenacity polyester yarn.

7. The method for preparing high-tenacity polyester yarn according to claim 6, characterized in that: In the step S2, during the spinneret extrusion process, the spinning temperature is controlled to be 260-300°C, and the cooling temperature is controlled to be 15-25°C.

8. The method for preparing high-tenacity polyester low-elastic yarn according to claim 6, characterized in that: In the step S3, during the heating deformation process, the stretching ratio is controlled to be 2-5, and the processing speed is controlled to be 500-800 m / min.

9. The method for preparing high-tenacity polyester low-elastic yarn according to claim 6, characterized in that: In the step S3, oiling is performed after false twisting, and the oiling rate is controlled to be 0.3-0.8wt%.

10. The method for preparing high-tenacity polyester low-elastic yarn according to claim 9, characterized in that: The oiling agent used in the step S3 comprises triphenyl phosphate, polyethylene glycol dioleate and castor oil polyoxyethylene ether in a weight ratio of 2-3:10-20:5-10.